Secondary School Teachers’ Conceptions of Teaching Science Practical Work through Inquiry-Based Instruction - Tomas Shivolo; Hamza Omari Mokiwa (Journal of Education in Science, Environment and Health)
Contemporary science teaching pedagogy in Namibia places a strong emphasis on fostering inquiry-based instruction and practical work in secondary school science education. In recent years, there has been a growing recognition of the need to move beyond traditional, rote-based methods towards more learner-centred approaches that encourage active inquiry and critical thinking. Teachers are encouraged to design lessons that promote inquiry, where learners actively investigate scientific phenomena, ask questions, and develop solutions through hands-on experimentation. Science practical work, which involves conducting experiments and investigations, is considered a cornerstone of this approach as it provides learners with opportunities to apply theoretical knowledge, develop laboratory skills, and gain a profounder understanding of scientific concepts. This sequential explanatory mixed methods study explored Namibian secondary school teachers’ conceptions of teaching science practical work through inquiry-based instruction to provide a comprehensive understanding of teachers’ perspectives and practices. Findings from this study revealed that many teachers held traditional views of science practical work, emphasizing cookbook-style experiments and memorisation. These teachers often faced challenges in implementing inquiry-based instruction due to a lack of training and resources to facilitate science practical work. However, a subset of teachers who embraced inquiry-based methods reported increased learner engagement, critical thinking, and in-depth understanding of scientific concepts. Additionally, the findings underscored the importance of aligning teacher conceptions with contemporary pedagogical approaches for effective secondary science education in Namibia. The study thus, highlighted the need for professional development and support to help more teachers transition to inquiry-based instruction and improve science education in Namibian secondary schools.